IMPLEMENTATION OF NEGOTIATIONS IN THE DIGITAL MARKETING PROJECT OF INDONESIAN SCHOOL STUDENTS IN KUALA LUMPUR: PRAGMATIC APPROACH - Sya'adah, Himatus; Yulianto, Bambang; Sodiq, Syamsul (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
In this digital era, students are active users of technology which make them connected to the outside world, either through social media, buying and selling sites, or online games. This phenomenon can be both a challenge and an opportunity. For this reason, one of the applications of the Kurikulum Merdeka is preparing the Indonesian generation as the driving force of the industrial era 4.0 and society 5.0 which is centered on a new technology-based society order. Negotiation practice is included in the first semester of Indonesian Language Learning Outcomes activities for class X. This research conducted in qualitative approach through field practice which aims to find students' negotiation patterns in digital-based marketing and entrepreneurship project practices on online platforms. The subjects in this study consisted in several groups in XB and XA class. The marketing target of the groups is the general public in Malaysia who like Indonesian culinary delights and online game users from various countries. Several groups who sell culinary product use code-mixing and code-switching in Malay, English, and Indonesian in marketing practices to get more consumers and transactions in ringgit currency. Meanwhile, the other group who trade in game platform use code-mixing and code-switching in Malay and English. The currency used in transactions is dollars. Digital media used for the project include other games, Instagram, and WhatsApp.